The Impact of The Service Quality of The Cleaning Staff of The Depot Logistics Employee Cooperative in The Servqual Model on Consumer Satisfaction at The East Nusa Tenggara Regional Office of Perum Bulog - Ludji Pa, Pieter Alexander; Kabanga, Margaretha S.; Manongga, Irience R. A. (CV. Jala Berkat Abadi, 2025)
In the era of globalization and increasingly fierce market competition, companies are racing to increase customer loyalty by focusing on service quality. Customer satisfaction is key to success, measured by perceptions of expectations influenced by objective quality and subjective interactions. Good service quality creates positive perceptions, satisfaction, and loyalty. Service quality indicators include physical evidence, empathy, reliability, responsiveness, and assurance. The theory used is from Tjiptono and Chandra (2016), expected service and perceived service. According to Husein Umar, quoted from his book Business Feasibility Studies (2005),